2009
DOI: 10.1074/jbc.m804813200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Huntingtin N-terminal Fragments of Specific Size Mediate Aggregation and Toxicity in Neuronal Cells

Abstract: Huntingtin proteolysis is implicated in Huntington diseasepathogenesis, yet, the nature of huntingtin toxic fragments remains unclear. Huntingtin undergoes proteolysis by calpains and caspases within an N-terminal region between amino acids 460 and 600. We have focused on proteolytic steps producing shorter N-terminal fragments, which we term cp-1 and cp-2 (distinct from previously described cp-A/cp-B). We used HEK293 cells to express the first 511 residues of huntingtin and further define the cp-1 and cp-2 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 42 publications
6
123
0
Order By: Relevance
“…The expanded polyQ stretch leads to an increased cleavage of mutant HTT by caspases and calpains, and results in an accumulation of toxic N-terminal HTT-fragments, which form aggregates in HD brains [41][42][43][44][45] . These fragments get degraded via the ubiquitin-proteasome pathway and by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The expanded polyQ stretch leads to an increased cleavage of mutant HTT by caspases and calpains, and results in an accumulation of toxic N-terminal HTT-fragments, which form aggregates in HD brains [41][42][43][44][45] . These fragments get degraded via the ubiquitin-proteasome pathway and by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal tag was chosen, because the N586 fragment of Htt is likely to undergo further N-terminal proteolysis. 29,30 Short N-terminal fragments of mutant Htt are believed to mediate its toxicity, possibly through aberrant protein interactions. By using a C-terminal tag, such interactions may be overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…Using the associative memory, water-mediated interactions, structure and energy model (AWSEM), previous simulations by our group have successfully explained how the change of critical nucleus size arises from the differences in the propensity of monomeric polyQ repeats of different lengths to form β-hairpins: the longer repeats fold into hairpins intramolecularly before they aggregate (9). The aggregation of the diseasecausing peptide is, however, further complicated by the presence of flanking amino acid sequences in fragments encoded by HTT exon 1. Experiments indicate that the addition of NT17 at the N terminus of polyQ enormously accelerates the aggregation, probably by encouraging the formation of prefibrillar oligomers (10)(11)(12)(13)(14)(15)(16), whereas the addition of the proline-rich region at the C terminus decreases the rate of aggregation apparently without changing fundamentally the mechanism (10,16,17). Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation.…”
mentioning
confidence: 99%